Efficient Greener Visible‐Light‐Catalyzed Debenzylation of Benzyl Ethers and Esters: A Gateway to Wider Exploitation of Stable Benzyl Protecting Groups. Issue 7 (1st June 2022) - Bhuyan, Samuzal; Mandal, Susanta; Jana, Saibal; Chhetri, Karan; Roy, Biswajit Gopal
Abstract: A non‐hydrogenolytic mild deprotection strategy for stable benzyl protection of hydroxyl group is one of the long‐cherished goals in multistep synthesis involving carbohydrates or compounds with multiple hydroxyl groups. A greener organo‐photocatalytic method has been developed for mild and efficient visible light catalytic deprotection of benzyl group from benzyl ether and benzyl ester. The newly developed method in ambient condition with only 1 mol% of catalyst loading can efficiently remove highly stable benzyl protection from ethers and esters of wide substrate scope with excellent functional group tolerance, thus proved to be suitable for final stage deprotection. Employment of molecular oxygen as terminal oxidant and excellent yield in the multigram scale reaction signifies the eco‐friendliness, robustness and industrial applicability of the method. Abstract : A greener synthetic methodology for visible‐light photocatalytic deprotection of stable benzyl group from benzyl ethers and benzyl esters has been reported. The method uses catalytic amounts of DDQ and only 1 mol% of easily synthesizable acridinium‐based photocatalyst, blue LED and aerobic oxygen as terminal oxidant for efficient debenzylation at room temperature.